Instagram as an Informative and Awareness-raising Medium on Migrant Minors: Good Practices from NGOs in Spain - Trillo Domínguez, Magdalena; Martín Neira, Juan Ignacio; Olvera Lobo, María Dolores (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2024)
NGOs are actively using social networks, specifically Instagram, to disseminate audiovisual content, with a strong emotional reaction, and to achieve effective and participatory communication that contributes to greater awareness and social mobilization. A recurring focus of interest in their campaigns is the situation of migrant minors, a vulnerable group that is frequently omitted and dehumanized. The aim of this work is to identify and highlight good practices from Spanish NGOs, a sensitive border territory and main gateway to Europe, so that they can be replicated in other geographical contexts to promote social change.